Comorbid Depressive and Anxiety Symptoms in a Patient with Myasthenia Gravis - Karthik R Cherukupally; Kodjovi Kodjo; Oluwaseun Ogunsakin; Olaniyi Olayinka; Patrice Fouron (Case Reports in Psychiatry)
Introduction. Myasthenia gravis (MG) is a chronic illness most commonly found in women under 40 years. The most common psychiatric comorbidities found in MG include depressive and anxiety disorders. Clinical Presentation. We describe a case of a 43-year-old African American female with MG who was brought in for shortness of breath. History included MG diagnosed twelve years prior to the current presentation and a history of seven intubations. The patient was admitted to the ICU and intubated. She endorsed poor sleep, easy fatigability, and feeling hopeless in the context of psychosocial stressors—being single, homeless, and unemployed. The patient was started on Zoloft 50 mg per oral daily for depression and Atarax 50 mg per oral three times a day for anxiety. The patient responded well to the treatment and was discharged on day 10 after the resolution of her symptoms with appropriate aftercare in place. Discussion. Depressive and anxiety symptoms usually develop as comorbidity during MG disease. Depressive and anxiety symptoms, besides motor symptoms, have a negative impact on the quality of life. Mental health must be a clinical focus during the treatment of somatic symptoms during MG.